G- and D-Cell Populations, Serum and Tissue Concentrations of Gastrin and Somatostatin in Patients with Peptic Ulcer Diseases - Park, Sill Moo (Korean J Intern Med, 1993)
BACKGROUND: Gastric acid is the most important pathophysiologic determinant in the development of peptic ulcer diseases, and gastrin and somatostatin are believed to be physiologic hormonal regulators in gastric acid secretion. The aim of this study is to investigate patterns of these peptides, both in serum and in tissue, and to correlate with numbers of their secretory cells in the antral and the duodenal bulb mucosa. METHODS: The study population was made up of 256 patients with peptic ulcer (duodenal ulcer, 127; gastric ulcer, 74) and 55 patients with non-ulcer control subjects. Serum and mucosal concentrations of G17, G34 and somatostatin were measured by radioimmunoassay technique and peptides producing cells were identified immunohistochemically using peroxidase-antiperoxidase staining technique. RESULTS: Serum G17 concentration was significantly decreased in duodenal ulcer patients (93.4±36.0 pg/ml) and G34 were more than twice as high as G17 both in patients with gastric and duodenal ulcer (210.6±50.6 pg/ml and 202.7±48.1 pg/ml vs 103.8±41.8 pg/ml and 93.4±36.0 pg/ml). Antral G17 (19.9±14.8 mcg/g, tissue) and G34 (26.6±18.5 mcg/g, tissue) were increased in duodenal ulcer patients and duodenal G17 (12.5±9.5 mcg/g. tissue in Gu and 8.5±7.4 mcg/g. tissue in DU) and G34 (15.7±12.6 mcg/g. tissue in GU and 13.9±12.0 mcg/g. tissue in DU) concentrations were found to be increased in both gastric and duodenal ulcer patients than in non-ulcer subjects (G17: 5.3±4.9 mcg/g. tissue. G34: 6.5±4.4 mcg/g. tissue). Only the antral somatostatin concentration was significantly increased in duodenal ulcer patients (5.3±5.9 mcg/g. tissue). Numbers of the antral G-and D-cell were lowest in GU patients (48.1±47.4 and 7.9±12.3) and numbers of both cells decreased proportionately with the severity of atrophic gastritis and/or intestinal metaplasia of the gastric mucosa. D/G cell ratio between non-ulcer subjects and DU patients was similar (1 : 4 and 1 : 5) but slightly increased in GU patients (1 : 7). There was no correlation between numbers of each peptide-producing cells and serum or mucosal concentration of gastrin and soamtostatin. CONCLUSIONS: Patients with duodenal ulcer had decreased level of serum G17 in the fasting state while mucosal concentrations of G17 and G34 were increased in the antrum and the duodenal bulb. Patients with garic ulcer had increased levels of G17 and G34 only in the duodenal bulb mucosa. Only the antral soamtostatin concentration was significantly increased in duodenal ulcer patients. Patients with gastric ulcer had lowest numbers of G- and D-cells in the antrum and numbers of both cells decreased proportionately with the degree of chronic atrophic gastritis and/or intestinal metaplasia of the gastric antrum. Numbers of G- and D-cells were not correlated with the serum or mucosal concentrations of each peptide.